Monetary Policy for an Open Economy: An Alternative Framework with Optimising Agents and Sticky Prices - Bennett T McCallum; Edward Nelson (Bank of England, External Monetary Policy Committee Unit, 2001)
The 'new open-economy macroeconomics' seeks to provide an improved basis for monetary and exchange-rate policy through the construction of open-economy models that feature rational expectations, optimising agents, and slowly adjusting prices of goods. This paper promotes an alternative approach for constructing such models by treating imports not as finished consumer goods but rather as raw-material inputs to the home economy's productive process. This treatment leads to a clean and simple theoretical structure that has some empirical attractions as well. A particular smalleconomy model is calibrated and its properties exhibited, primarily by means of impulse response functions. The preferred variant is shown to feature a pattern of correlations between exchange-rate changes and inflation that is more realistic than provided by a more standard specification. Important recent events are interpreted in light of the alternative models.
Keywords: 330; new open economy macroeconomics; monetary policy rules; exchange rates and inflation.